An Analysis of Teacher’s Strategy in Teaching Public Speaking at Aviation School of Nusantara Tjahja Cipta Sidoarjo - Halisah, Siti Nur; Megawati, Fika (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This research was aimed to find out what are the teacher's strategies in teaching public speaking at Aviation School Nusantara Tjahja Cipta Sidoarjo with the qualitative descriptive method and used the Class observation documentation and Semi-Structured In-Dept Interview as the Instrumental data. Furthermore, the subject of this research was an English teacher. For the research results, the researcher concluded that in teaching public speaking, the English teacher used several strategies as follows: Pedagogical Principles (Experience-Based an Incremental Approach), Communication Apprehension Management, Practical, and Scoring. In the pedagogical Principle-strategy, the teacher implemented lecturing brainstorming activities to help students understanding the materials in detail and comprehensively. The second strategy that used was Communication Apprehension Management, in this kind of activity, the public speaking teacher implemented a variety of communication interactions by making a sharing session. Third, for the practical strategy, the public speaking teacher was giving the two kinds of assessments such as speaking groups of presentation and role-play dialogue conversation. The last in the strategy of scoring, the teacher evaluated and assessed regarding the students’ attendance and the presentations.